UPAYA PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA PADA SISWA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED-HEAD TOGETHER (NHT) - Widodo, Widodo (UNIVERSITAS SLAMET RIYADI, 2019)
Abstract. This classroom action research aims to describe the improvement of students’ learning activity and their learning result through cooperative learning in the form of Numbered-head Together (NHT). The study was done in two cycles, involving 34 students of grade III of MI Negeri Grogol in the first semester of 2016/2017 academic year. The results of the study are as follows: 1) There was an improvement on students’ learning activity score, starting from 2.51 (less engaged) to 3.83 (highly engaged) in cycle I, 2) students’ average score on their learning result improved, starting from 65.91 (with maximum score of 85 and 35.29% or 12 students reaching the passing grade) in the prior stage to 79.74 (with minimum score of 100 and minimum score of 55 and 82.35% or 28 students reaching the passing grade) in Cycle II.Keywords: learning activity, learning result, Numbered-head Together (NHT) Abstrak.Penelitian ini merupakan Penelitian Tindakan Kelas, bertujuan mendeskripsikan peningkatan aktivitas dan hasil belajar siswa dengan model pembelajaran kooperatif tipe Numbered-Head Together (NHT), dilakukan 2 siklus. Siswa yang diteliti kelas III (Tiga) MI Negeri Grogol semester 1 TP 2016/2017 yang berjumlah 34 siswa. Hasil penelitian ;. 1) Nilai rerata aktivitas kondisi awal 2.51 (Kurang Aktif). Kondisi akhir siklus II nilai rerata 3,83 (Sangat Aktif) . 2) Hasil belajar Matematika kondisi awal nilai tertinggi 85, nilai rerata 65.91. Ketuntasan siswa 12 siswa (35.29%). Kondisi akhir siklus II dengan nilai terendah 55, nilai tertinggi 100, nilai rerata 79.74 dan sebanyak 28 siswa (82.35%) mencapai nilai KKM.Kata kunci: aktivitas belajar, hasil belajar, Numbered-Head Together (NHT)